2012
DOI: 10.1159/000331143
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Natural-Like Recombinant Der p 2 for Sublingual Immunotherapy

Abstract: Background: Recombinant allergens with a native conformation represent an alternative to natural extracts for immunotherapy and diagnostic purposes. Methods: We produced the Der p 2 mite allergen in Pichia pastoris and Escherichia coli. After purification by cation exchange chromatography, recombinant molecules were compared to their natural counterpart based upon structural (disulfide bonds, secondary structure, thermal stability) and immunological properties (antibody reactivity, basophil and T cell activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 108 publications
0
17
0
Order By: Relevance
“…As previously reported, nonglycosylated PMEs like that of Diospyros kaki conserved their 3-dimensional folding and its enzymatic activity when comparing with other glycosylated PMEs [34]. Thus, we expressed Sal k 1-specific cDNA in bacteria because glycosylation should not be critical for the 3-dimensional folding of PMEs [34], and it has also been successfully used to express other glycosylated allergens, which maintained intact structural and immunological properties [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, nonglycosylated PMEs like that of Diospyros kaki conserved their 3-dimensional folding and its enzymatic activity when comparing with other glycosylated PMEs [34]. Thus, we expressed Sal k 1-specific cDNA in bacteria because glycosylation should not be critical for the 3-dimensional folding of PMEs [34], and it has also been successfully used to express other glycosylated allergens, which maintained intact structural and immunological properties [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Olsson et al [ 49 ] reported that recombinant Lep d 2 expressed in E. coli or in S. frugiperda had IgE- binding and basophil activation activities similar to the native protein. Bordas-Le Floch et al [ 50 ] found that recombinant Der p 2 expressed in E. coli did have structural differences detected by circular dichroism but had Ig-E binding and basophil stimulation activities comparable to those of the native or recombinant Der p 2 expressed in P. pastoris . In contrast, Der p 1 or Der f 1 expressed in E coli had significantly less IgE-binding activity when compared to the native form [ 51 ].…”
Section: Confirmation Phasementioning
confidence: 99%
“…Additionally, for purification of allergen homologues, cross-reactive antibodies identified in one species can be applied to a new species [ 18 ]. In the absence of specific antibodies, alternative chromatography techniques, including ion exchange, gel filtration and hydrophobic exchange, have been used to fractionate whole mite or feces extracts [ 6 , 27 , 30 , 50 ]. Fractions were then tested for IgE-binding activity and/or desired enzymatic activity [ 6 ] and assayed for homogeneity.…”
Section: Confirmation Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Because of this high reactivity, recombinant groups 1 and 2 allergens have been generated from Dermatophagoides pteronyssinus . However, the recombinant Der p 1 is only weakly reactive, while the recombinant Der p 2 exhibits IgE reactivity comparable to the native allergen . Although the groups 1 and 2 allergens are the major allergens from Dermatophagoides spp., other allergens from these species contribute to allergic disease.…”
Section: Introductionmentioning
confidence: 99%